IDENTIFIKASI TUMBUHAN PAKU EPIFIT PADA HUTAN JUATA KERIKIL KOTA TARAKAN KALIMANTAN UTARA - Robianto Robianto; Inda Permatasari; Hasdar Hasdar; Mega Aditiyanto (Biopedagogia, 2020)
This study aims to identify the species of ferns in the Hutan Lindung RPH Barat (Juwata Kerikil). The research method used adaptive sampling technique. In the identification results of epiphytic ferns in Hutan Lindung RPH Barat (Juwata Kerikil), 8 species of ferns have been identified. The largest family found is Polypodiaceae with 6 species, consisting of Pyrrosia piloselloides, Platycerium bifurcatum, Drynaria sparsisora, Drymoglossum piloselloides, Pyrrosia longifolia, and Pyrrosia lanceolata. Meanwhile, the Aspleniaceae and Davalliaceae families were only found each one species, namely Asplenium nidus and Davallia solida. Keywords: Ferns, Epiphytes